Flower‐visiting insects and their potential impact on transgene flow in rice. Issue 5 (27th June 2014) - Pu, De‐qiang; Shi, Min; Wu, Qiong; Gao, Ming‐qing; Liu, Jia‐Fu; Ren, Shao‐peng; Yang, Fan; Tang, Pu; Ye, Gong‐yin; Shen, Zhi‐cheng; He, Jun‐hua; Yang, Ding; et al.
Summary Rice is one of the most important crops in the world. Several transgenic varieties of rice have been developed, and some have recently entered pre‐production trials. One concern with genetically modified (GM) crops is transgene escape, but prior studies suggest this risk is low for rice because it is self‐pollinated and the dispersal of pollen by wind is limited. Little is known about the impact of pollen transport by insects. We characterized the insects visiting rice plants during anthesis and considered the effects of insect pollination on gene flow. We conducted a 2‐year nationwide survey in China and identified more than 510 insect species that visited rice flowers. Honeybees, hoverflies and several other species carried large amounts of pollen. The European honeybee Apis mellifera visited rice flowers regularly with daily foraging activity peaking between 12.00 and 13.00 h. We monitored 20 European honeybee colonies located 100–1000 metres away from rice fields in mixed agricultural landscapes and found the honeybees carried viable pollen at least 500 m away from the rice pollen source. We used four GM rice lines as pollen donors, their non‐GM parental varieties as pollen recipients and the European honeybee as the pollinator in field‐cage experiments to assess whether honeybees increase the frequency of gene flow in rice. Results from screening over 1·5 million germinated offspring seeds over a 3‐year study period showed that honeybees significantly increase transgene flow in rice. Synthesis and applications. Our results indicate that a remarkably high diversity of insects visit rice flowers in China and that hundreds of species including honeybees carry large amounts of rice pollen. European honeybees carry viable pollen over long distances, forage on rice flowers regularly and increase the frequency of transgene flow. Insects mediate gene flow in rice more than previously assumed, and this should be taken into consideration during the ecological risk assessment of transgene flow in self‐pollinated and/or anemophilous crops.